2020
DOI: 10.1111/ajo.13162
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of sonographic estimation of weight in fetuses with abdominal wall defects

Abstract: Background: Accurate estimation of fetal weight is essential in guiding management of fetuses with abdominal wall defects (AWDs), as growth restriction is an important predictor of perinatal morbidity and mortality. Several sonographic formulae are available involving multiple biometric parameters, but abdominal circumference measurements may underestimate weight in fetuses with AWDs. No formula has yet shown superior accuracy. Aims: The objectives of this study were to evaluate, in fetuses with gastroschisis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Na gastrosquise o problema é diretamente associado com exposição visceral ao líquido amniótico e subsequente perda proteica. Já na onfalocele a restrição de crescimento é menos comum e geralmente associada à síndromes genéticas e outras malformações (14)(15)(16).…”
Section: Resultsunclassified
“…Na gastrosquise o problema é diretamente associado com exposição visceral ao líquido amniótico e subsequente perda proteica. Já na onfalocele a restrição de crescimento é menos comum e geralmente associada à síndromes genéticas e outras malformações (14)(15)(16).…”
Section: Resultsunclassified
“…The traditional threshold of EFW less than the 10th percentile Previous studies evaluating ultrasound prediction of FGR in fetuses with gastroschisis have focused on EFW obtained as close to delivery as possible compared to actual birth weights, and some included fetuses with omphalocele. 8,9,[21][22][23][24][25] Nicholas et al found the Hadlock I formula to be the best screening test for FGR. In their study, the Hadlock formula had better specificity when compared to the Siemer formula, which excluded the abdominal circumference (AC) in its calculations.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 This has prompted investigation of alternative EFW equations which do not include the AC measurement. 5,7,8 Fetuses with gastroschisis have a higher incidence of fetal growth restriction (FGR) compared with those without abdominal wall defects. 6 Infants with gastroschisis whose birth weights are less than the tenth percentile fare worse than those with higher birth weight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Omphalocele is a AWD at the umbilicus, and the viscera outside the belly are covered by a membrane 2 4 . Patients with AWDs have an increased incidence of intrauterine growth restriction, and, therefore, the estimation of weight in fetuses with AWDs during gestational ultrasonography is more difficult than for normal fetuses 5 7 .…”
Section: Introductionmentioning
confidence: 99%